2013
DOI: 10.1007/s11306-013-0520-2
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabonomics of bovine blood: an investigation into the effects of long term storage on plasma samples

Abstract: Trabi, M., Keller, M.D., and Jonsson, N. (2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…However, further testing did not indicate that differences in the metabolomes of matched samples appeared after long-term storage (−80 °C) (Figure 3d–f, Table S3). This is corroborated by previous investigations that tested the influence of storage (−80 °C) duration on metabolite concentrations [24,25]. Previous studies on the impact of long-term (e.g., years) storage on the metabolome have involved relatively short time frames or have not been performed on replicate samples, instead relying on different samples from similar populations, but have shown that storage affected the concentrations of only a few metabolites [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…However, further testing did not indicate that differences in the metabolomes of matched samples appeared after long-term storage (−80 °C) (Figure 3d–f, Table S3). This is corroborated by previous investigations that tested the influence of storage (−80 °C) duration on metabolite concentrations [24,25]. Previous studies on the impact of long-term (e.g., years) storage on the metabolome have involved relatively short time frames or have not been performed on replicate samples, instead relying on different samples from similar populations, but have shown that storage affected the concentrations of only a few metabolites [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…The optimal time is considered to be no more than 35 min and preferably over ice, as longer waiting time may increase lactate levels due to continued glucose metabolism in blood cells [45]. However, limited data are available on long-term storage, although a recent pilot study of heparinized bovine plasma samples stored for up to 15 years reported minimal effects [47]. However, limited data are available on long-term storage, although a recent pilot study of heparinized bovine plasma samples stored for up to 15 years reported minimal effects [47].…”
Section: Pre-analytical Stepsmentioning
confidence: 99%
“…Lactate is the most abundant low-weight metabolite we were able to observe in the yak serum. In cattle, its presence has been mainly attributed to ruminal microflora [29]. Its presence in yak serum plays a special role, because its high concentration, together with pyruvate, is a direct consequence of the adaptation to low oxygen levels connected to altitude [30,31,32].…”
Section: Discussionmentioning
confidence: 99%